Local Processing Bias Impacts Implicit and Explicit Memory in Autism - Lebreton, Karine; Malvy, Joëlle; Bon, Laetitia; Hamel-Desbruères, Alice; Marcaggi, Geoffrey; Clochon, Patrice; Guénolé, Fabian; Moussaoui, Edgar; Bowler, Dermot M.; Bonnet-Brilhault, Frédérique; Eustache, Francis; Baleyte, Jean-Marc; et al. (Frontiers in Psychology, 2021)
Autism spectrum disorder (ASD) is characterized by atypical perception, including processing that is biased towards local details rather than global configurations. This bias may impact on memory. The present study examined the effect of this perception on both implicit (Experiment 1) and explicit (Experiment 2) memory in conditions that promote either local or global processing. The first experiment consisted of an object identification priming task using two distinct encoding conditions: one favoring local processing (Local condition) and the other favoring global processing (Global condition) of drawings. The second experiment focused on episodic (explicit) memory with two different cartoon recognition tasks that favored either local (i.e. processing specific details) or a global processing (i.e. processing each cartoon as a whole). In addition, all the participants underwent a general clinical cognitive assessment aimed at documenting their cognitive profile and enabling correlational analyses with experimental memory tasks. Sixteen participants with ASD and 16 typically developing (TD) controls aged from 10 to 16 years participated to the first experiment and 13 ASD matched with 13 TD participants were included for the second experiment. Experiment 1 confirmed the preservation of priming effects in ASD but, unlike the Comparison group, the ASD group did not increase his performance as controls after a globally-oriented processing. Experiment 2 revealed that local processing led to difficulties in discriminating lures from targets in a recognition task when both lures and targets shared common details. The correlation analysis revealed that these difficulties were associated with processing speed and inhibition. These preliminary results suggest that natural perceptual processes oriented toward local information in ASD may impact upon their implicit memory by preventing globally-oriented processing in time-limited conditions and induce confusion between explicit memories that share common details.